GPR41 and GPR43 regulate CD8+ T cell priming during herpes simplex virus type 1 infection - Lee, Ariane Renita; Wilson, Kayla Roberta; Clarke, Michele; Engel, Sven; Tscharke, David C.; Gebhardt, Thomas; Bedoui, Sammy; Bachem, Annabell (Frontiers in Immunology, 2024)
Naïve CD8+ T cells need to undergo a complex and coordinated differentiation program to gain the capacity to control virus infections. This not only involves the acquisition of effector functions, but also regulates the development of a subset of effector CD8+ T cells into long lived and protective memory cells. Microbiota-derived metabolites have recently gained interest for their influence on T cells, but much remains unclear about their role in CD8+ T cell differentiation. In this study, we investigated the role of the G protein-coupled receptors (GPR)41 and GPR43 that can bind microbiota-derived short chain fatty acids (SCFAs) in CD8+ T cell priming following epicutaneous herpes simplex virus type 1 (HSV-1) infection. We found that HSV-specific CD8+ T cells in GPR41/43-deficient mice were impaired in the antigen-elicited production of interferon-gamma (IFN-γ), tumour necrosis factor-alpha (TNF ), granzyme B and perforin, and failed to differentiate effectively into memory precursors. The defect in controlling HSV 1 at the site of infection could be restored when GPR41 and GPR43 were expressed exclusively by HSV-specific CD8+ T cells. Our findings therefore highlight roles for GPR41 and GPR43 in CD8+ T cell differentiation, emphasising the importance of metabolite sensing in fine-tuning anti-viral CD8+ T cell priming.